2018
DOI: 10.3390/ijms20010038
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Functionally Active Extracellular Vesicles from Culture Medium Conditioned by Bovine Embryos In Vitro

Abstract: Extracellular vesicles (EVs) play a possible role in cell–cell communication and are found in various body fluids and cell conditioned culture media. The aim of this study was to isolate and characterize EVs in culture medium conditioned by bovine embryos in group and to verify if these EVs are functionally active. Initially, ultracentrifuged bovine serum albumin (BSA) containing medium was selected as suitable EV-free embryo culture medium. Next, EVs were isolated from embryo conditioned culture medium by Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 40 publications
0
60
0
2
Order By: Relevance
“…Earlier, Mellisho et al [21] have demonstrated that 500 µL of medium conditioned by bovine blastocysts was sufficient for EV isolation, but apparently, in this study, no standardized EV isolation method was applied. In our previous study, initially, we used 500 µL of embryo-conditioned medium, but this was not sufficient for either characterization or quantification of EVs [6]. In conclusion, the separation of EVs with high specificity from 1 mL of embryo culture medium was addressed in the current study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Earlier, Mellisho et al [21] have demonstrated that 500 µL of medium conditioned by bovine blastocysts was sufficient for EV isolation, but apparently, in this study, no standardized EV isolation method was applied. In our previous study, initially, we used 500 µL of embryo-conditioned medium, but this was not sufficient for either characterization or quantification of EVs [6]. In conclusion, the separation of EVs with high specificity from 1 mL of embryo culture medium was addressed in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Routine in vitro methods were used for bovine embryo production, as described previously by Pavani et al [6]. Briefly, at the local abattoir, cow ovaries were obtained and processed within 2 h after collection.…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not only the number of EVs released into extracellular space but also the molecular cargo of those EVs, which was differed between male and female exposed to OS. As shown in Figure , EVs from male embryos at higher oxygen level contained higher level of NFE2L2 and SOD1 transcripts compared to those cultured under low oxygen level, which might be beneficial of development of embryos (Pavani et al, ). The role of EVs is not only in cell–cell communication (Saeed‐Zidane et al, ) but also in the removal of undesirable cellular molecules (Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 99%